Regional Groundwater Water Quality Assessment and Contamination Source Identification by a Self-Organizing Map and Entropy Method in Pinggu Basin, Northeast Beijing - Lv, Shaojie; Zhang, Zongwen; Sun, Ning; Shi, Zheming; Li, Jia; Qu, Shen (Frontiers in Environmental Science, 2022)
Groundwater quality assessment is important in understanding the suitability of groundwater resources for various purposes. Although many different methods have been proposed for the purpose, few methods have considered the spatial and temporal variation of the groundwater components in the assessment process. In this study, we proposed to combine Self-Organizing Map (SOM) and entropy based weight determining method to assess the groundwater quality. A total of 955 water samples taken from 58 wells during 2010-2017 were used in the study. 22 hydrochemical components (K+, Na+, Ca2+, Mg2+, NH4+, Cl-, SO42-, F-, NO3-, Fe2+, Fe3+, Al, etc.) were used in the assessment for each sample. These sampling points can be classified into five clusters, which may be affected by four different sources: landfill sources (cluster 3), industrial and agricultural sources (cluster 5), domestic sewage discharge sources (clusters 1, 2 and 4). The score of water quality of the five clusters that calculated by the entropy method are 0.2658, 0.2634, 0.5737, 0.2608, 0.5718, indicating that the groundwater affected by domestic sewage discharge sources (clusters 1, 2 and 4) are better than that by other two sources (clusters 3 and 5) in the study area. The results of this study show that the combination of these two methods is efficient in assessing region groundwater quality and also provides a method for identifying potential sources of contamination.